Discovering the Hidden Work of Commodified Care: The Case of Early Childhood Educators - Frances Press; Michael Bittman; Linda Joan Harrison; Judith E. Brown; Sandie Wong; Megan Gibson (Social Sciences)
The COVID-19 pandemic has drawn attention to the care economy, including commodified early childhood education and care (ECEC). While there is some literature about the low paid, invisible, and undervalued skills among the predominantly female workforce in the ECEC sector, there is little research into what these educators do in their working day and how this contributes to quality education and care for young children. This article provides a detailed examination of ten defined domains of ECEC work tasks, derived from data generated by educators’ use of ‘intensive hour’ time-diary methodology. The results reveal that the outstanding characteristics of this occupation are multi-tasking and the rapid switching of tasks as educators manage diverse expectations arising from work with groups of very young children, families, other staff, and meeting legislated responsibilities. Drawing on William J. Baumol’s economic theory, we consider the implications for productivity and cost tensions in ECEC.